2015
DOI: 10.1007/s00228-015-1878-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the interchangeability of generic formulations using immunosuppressants and a broad selection of medicines

Abstract: PurposeTo date, the interchangeability of generic drugs has only been investigated for a limited number of medicines. The objective of this study was to investigate generic-generic drug interchangeability in a large subset of generic formulations in order to cover a broad spectrum of drugs.MethodsOrally administered drugs for investigation in this study were selected using strict, predefined criteria, with the purpose to avoid bias. This selection procedure yielded atorvastatin, bicalutamide, naratriptan, olan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 30 publications
3
29
0
3
Order By: Relevance
“…ASERTAA (A Study of Extended Release Tacrolimus in African Americans) was an open-label, prospective, randomized, 2-sequence, 3-period, crossover, pharmacogenetic study conducted at the University of Pennsylvania, University of Illinois, and Washington University School of Medicine (St. Louis) between November 25, 2013, and July 30, 2015 ( Fig 1). The main study objective was to compare steady-state pharmacokinetics of once-daily LCPT tablets (dosed 15% lower than total daily IR-Tac dose) with evenly divided twice-daily IR-Tac capsules (Prograf [Astellas Pharma US, Inc] or its generic formulations [predominately Sandoz, Dr Reddy, and Accord formulations], for which the systemic exposure differs minimally compared to Prograf [35][36][37] ) in stable African American kidney recipients, according to CYP3A5 genotype. Secondary objectives were to confirm the total daily dose reduction in the LCPT group following conversion from IR-Tac and compare the safety and short-term efficacy of the 2 formulations.…”
Section: Study Design and Objectivesmentioning
confidence: 99%
“…ASERTAA (A Study of Extended Release Tacrolimus in African Americans) was an open-label, prospective, randomized, 2-sequence, 3-period, crossover, pharmacogenetic study conducted at the University of Pennsylvania, University of Illinois, and Washington University School of Medicine (St. Louis) between November 25, 2013, and July 30, 2015 ( Fig 1). The main study objective was to compare steady-state pharmacokinetics of once-daily LCPT tablets (dosed 15% lower than total daily IR-Tac dose) with evenly divided twice-daily IR-Tac capsules (Prograf [Astellas Pharma US, Inc] or its generic formulations [predominately Sandoz, Dr Reddy, and Accord formulations], for which the systemic exposure differs minimally compared to Prograf [35][36][37] ) in stable African American kidney recipients, according to CYP3A5 genotype. Secondary objectives were to confirm the total daily dose reduction in the LCPT group following conversion from IR-Tac and compare the safety and short-term efficacy of the 2 formulations.…”
Section: Study Design and Objectivesmentioning
confidence: 99%
“…AICs have been adopted as a useful tool for assessing bioequivalence between generic products and their switchability, as well as for comparing originator products from different markets that have previously been shown to be bioequivalent with the same generic product . To our knowledge, this is the first study to compare clopidogrel generic products.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons between generics are not performed as there is no regulatory requirement for conducting these studies since they are not practical . Therefore, the adjusted indirect comparisons (AICs) are the most suitable method to assess bioequivalence between generics . To our knowledge, generic products of clopidogrel have not been compared between themselves, neither indirectly nor directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Further, secondary analysis of 120 bioequivalence studies on 3 immunosuppressants and 6 selected drugs calculated a mean generic-generic deviation of 4.5 % for AUC T and 5.1 % for C max . [27] The data together suggest that, at a group level, most of the product-product deviations observed in typical bioequivalence studies may not be related to using 2 different products but can be observed when comparing a single drug product to itself.…”
Section: Extent Of Average Bio-variability Of a 200 Mg Caffeine Productmentioning
confidence: 96%